2021
DOI: 10.7759/cureus.19751
|View full text |Cite
|
Sign up to set email alerts
|

Pakistan Ranks Third Globally With the Most Unvaccinated Children: Is the Impact of Parental Perception and Attitude on Immunization an Essential Contributing Factor to an Unsuccessful Vaccination Coverage?

Abstract: Introduction Having the third-highest burden of child mortality and ranking third globally for the most under-vaccinated children, Pakistan contains 15% of its population under the age of five, which accounts for 50% of the mortality rate in this country. Every year, almost three million children miss out on an entire course of the most readily available vaccines, leaving them vulnerable to life-threatening diseases. The Expanded Program of Immunization (EPI) was launched in 1978 to protect children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…Saeedet al, conducted a study in Karachi to assess vaccination rate of children, found 91% of parents had skipped one or more vaccines of EPI schedule which closely resembles our finding of 89% [4]. Most frequent cause of skipping vaccination was unavailability of vaccines (19.8%) followed by long distance to vaccination facility (18.7%).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Saeedet al, conducted a study in Karachi to assess vaccination rate of children, found 91% of parents had skipped one or more vaccines of EPI schedule which closely resembles our finding of 89% [4]. Most frequent cause of skipping vaccination was unavailability of vaccines (19.8%) followed by long distance to vaccination facility (18.7%).…”
Section: Discussionsupporting
confidence: 81%
“…Socioeconomic status of parents did not appear a significant factor for poor immunization in our study. However, Saeed et al, and Khattak et al, have reported it a significant factor in their studies [4,13]. Lucyk et al, reviewed the literature and found 52.4% articles showing significant association between socioeconomic status and pediatric immunization, 4.5% showed negative association and 14.3% revealed no association [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 The EPI was launched in Pakistan in 1978, and provides protection from deadly yet preventable childhood diseases such as Tuberculosis, Diphtheria, Rotavirus, and Poliomyelitis. 9 In Pakistan, rampant vaccine hesitancy and barriers to provide vaccinations have deprived about 3 million Pakistani children annually from acquiring a full course of childhood vaccinations, despite it being widely available. One major reason for vaccine hesitancy amongst parents was vaccine hesitancy, with one poll depicting 77% of parents expressing concerns regarding childhood vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…7 , 8 Children under 5 comprise of only 15% of the population, yet make up 50% of the mortality rate. 9 These statistics do not reflect the true situation due to a lack of a functioning disease surveillance system, as well as inadequate data on births and deaths. 10 However, Pakistan has the highest ratio in Asia for infant mortality from diarrhea.…”
Section: Introductionmentioning
confidence: 99%